Association of Serum Bicarbonate With Risk of Renal and Cardiovascular Outcomes in CKD: A Report From the Chronic Renal Insufficiency Cohort (CRIC) Study - Dobre, Mirela (2013)
BACKGROUND: The purpose of this study is to evaluate serum bicarbonate as a risk factor for renal outcomes, cardiovascular events and mortality in patients with chronic kidney disease (CKD). STUDY DESIGN: Observational cohort study. SETTING & PARTICIPANTS: 3939 participants with CKD stages 2-4 who enrolled in the Chronic Renal Insufficiency Cohort (CRIC) between June 2003 - December 2008. PREDICTOR: Serum bicarbonate. OUTCOMES: Renal outcomes, defined as end-stage renal disease (either initiation of dialysis or kidney transplantation) or 50% reduction in eGFR; atherosclerotic events (myocardial infarction, stroke, peripheral arterial disease); congestive heart failure events; and death. MEASUREMENTS: Time to event. RESULTS: The mean eGFR was 44.8 ± 16.8 (SD) mL/min/1.73 m(2), and the median serum bicarbonate was 24 (IQR, 22-26) mEq/L. During a median follow-up of 3.9 years, 374 participants died, 767 had a renal outcome, and 332 experienced an atherosclerotic event and 391 had a congestive heart failure event. In adjusted analyses, the risk of developing a renal endpoint was 3% lower per mEq/L increase in serum bicarbonate (HR, 0.97; 95% CI, 0.94-0.99; p=0.01). The association was stronger for participants with eGFR> 45ml/min/1.73m(2) (HR, 0.91; 95%CI, 0.85-0.97; p=0.004). The risk of heart failure increased by 14% (HR, 1.14; 95%CI, 1.03-1.26; p=0.02) per mEq/L increase in serum bicarbonate over 24 mEq/L. Serum bicarbonate was not independently associated with atherosclerotic events (HR, 0.99; 95%CI, 0.95-1.03; p=0.6) and all-cause mortality (HR, 0.98; 95%CI, 0.95-1.02; p=0.3). LIMITATIONS: Single measurement of sodium bicarbonate. CONCLUSIONS: In a cohort of participants with CKD, low serum bicarbonate was an independent risk factor for kidney disease progression, particularly for participants with preserved kidney function. The risk of heart failure was higher at the upper extreme of serum bicarbonate. There was no association between serum bicarbonate and all-cause mortality or atherosclerotic events.